2020
DOI: 10.21203/rs.2.20263/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers for Full Immunization Coverage among under Five Years Children in  Mogadishu, Somalia

Abstract: Background: Immunization is amongst the most cost effective public health interventions for reducing global childhood morbidity and mortality. However globally 9 million deaths of children occur as a result of vaccine-preventable disease, a bigger proportion occurred in sub-Saharan Africa which was 4.4 million. Therefore, this study aimed to assess barriers for complete vaccination coverage among under five years children in Mogadishu, Somalia. Methods: A community based Cross-sectional study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Caregivers who had positive perceptions of immunization were nearly five times more likely to immunize their children than those who had a neutral perception of immunization (AOR = 4.976, 95% CI: 2.183–11.340, P value = 0.001). This result is in line with the finding from the previous study in Somalia by[ 9 ] that showed “children's immunization status was significantly associated with caregivers’ positive perceptions on the usefulness of immunizations to children.”…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Caregivers who had positive perceptions of immunization were nearly five times more likely to immunize their children than those who had a neutral perception of immunization (AOR = 4.976, 95% CI: 2.183–11.340, P value = 0.001). This result is in line with the finding from the previous study in Somalia by[ 9 ] that showed “children's immunization status was significantly associated with caregivers’ positive perceptions on the usefulness of immunizations to children.”…”
Section: Discussionsupporting
confidence: 92%
“…[ 8 ] UNICEF, 2010 reported that the immunization coverage of under-5 children in Mogadishu was 40%. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunization is achieved by a variety of methods, the most common is vaccination (WHO/UNICEF, 2005), (Hassan, 2020), (Mohamud et al, 2020). Vaccination is regarded as one of the most successful, safe and cost-effective public health intervention for reducing child morbidity and mortality from infectious illnesses.…”
Section: Immunization Dropoutmentioning
confidence: 99%
“…An estimated 2.5 million children aged less than 5 years die annually due to diseases that can be prevented by vaccination ( Tefera et al, 2018 ; Aregawi et al, 2017 ; Adokiya, Baguune & Ndago, 2017 ). About 14.8 million children who are not vaccinated with pentavalent 3 before celebrating their first year are found only in only 10 countries, including Ethiopia ( Yenit, Gelaw & Shiferaw, 2018 ; Aregawi et al, 2017 ; Mihigo et al, 2017 ; Adokiya, Baguune & Ndago, 2017 ; Mohamed et al, 2016 ). Despite the fact that most under-five deaths can be easily tackled by vaccination, about half occur in SSA ( WHO, 2015 ; Federal Ministry of Health of Ethiopia, 2012 ; Adedire et al, 2017 ; Shemwella et al, 2017 ; Kassahun, Biks & Teferra, 2015 ; Debie & Taye, 2014 ; Mohamud et al, 2014 ; Legesse & Dechasa, 2015 ; Ebrahim & Salgedo, 2015 ; Facha, 2015 ).…”
Section: Introductionmentioning
confidence: 99%